Integrasi dan Pengaruh Pendekatan Politik dan Sosial dalam Historiografi Islam - Abdullah Husen; Moh MusyfiqKhazin (Khulasah : Islamic Studies Journal, 2026)
Islamic history encompasses the events occurring within the Muslim Ummah from the birth of Islam to the present day. In the historiography of Islam, two primary methods of writing are utilized: political and social. This paper examines the characteristics of these two methods. Political historiography of Islam is identified with the ruling dynasties throughout Islamic history, divided into three periods: classical, medieval, and modern. On the other hand, the social history of Islam offers a broader and multidimensional observation, maintaining that Islamic history is not solely defined by political movements. Historiography that focuses exclusively on periods of power tends to overlook many historical events, as aspects of human life beyond politics are not included as subjects of historical study.